Pengembangan Lembaga Pendidikan Unggulan Berbasis Aswaja Pada Sekolah Dasar Unggulan Muslimat NU Kudus - Selamet Syaifuddin (Sekolah Tinggi Agama Islam Pati, 2022)
Excellent educational institutions are institutions that develop the uniqueness of the school in a learning to be mastered by students. The purpose of this study is to describe the management of social capital in developing superior educational institutions in the local area. The object of the study is an educational institution founded by Muslimat NU Branch Kudus, namely SD Muslimat NU Superior. This study uses a qualitative approach. Data was collected through observation, interviews and documentation. In this study, researchers used a single case analysis technique (single case design). The analysis process is carried out simultaneously with data collection through several stages through the process of data collection, data reduction, data presentation and verification or drawing conclusions. The results show that building and managing social capital appropriately is able to build superior institutions in a faster time. The three main elements of social capital are: trust, which is built from exemplary moral education, knowledge and skills. The manifestation of this trust is the formation of the suggestion “My School is My Home.”; networks (networks are built based on communication, involvement and coordination; while shared values are based on discipline, hard work, togetherness, simplicity, independence, patience and tolerance which are the elaboration of the values contained in Aswaja.